Concentration of "Mysterious Solute" in CoCrFeNi high entropy alloy. (1st April 2022) - Yang, Yingjian; Li, Zhongtao; Zhang, Weidong; Ma, Yi; Xiong, Qingang; Li, Weidong; Chen, Shuying; Wu, Zhenggang
Abstract: The appearance of serrated flow on stress-strain curves in single-phase high entropy alloys (HEAs) suggests that their lattices are arranged and behave differently than those in pure metals. In this study, a micromechanical model linking serration amplitude and solute concentration difference at the dislocation line was built to quantify the concentration of "mysterious solute" in HEAs. Using the model, the concentration of "mysterious solute" in a model HEA, CoCrFeNi, was determined to be ∼34 at.%. Despite that certain facets of the physical nature of the solute remains to be further delved into, our present findings indeed suggest a quantitative distinction between the solvent and solute in single-phase HEAs. As opposed to commonly treating these concentrated solid solutions as an average "medium", our work paves the avenue of separating out the solute and solvent, which is beneficial to unveiling many key questions in HEAs (e.g., obstruction of the solute to dislocation motion). Graphical abstract: Image, graphical abstract